The World Republic, The State of States or The League of Nations? Kant’s Global Order Revisited - Wyrębska-Đermanović, Ewa (Con-Textos Kantianos. International Journal of Philosophy, 2019)
The article investigates the problem of Kant’s proposal for a final global legal order. Kant expressed his stance very vaguely in the consecutively published texts On the Common Saying, Toward Perpetual Peace and The Metaphysics of Morals, which enabled numerous, often contradictory interpretations. The aim of the paper is to propose an alternative method of analysis of Kant’s texts, which on one side reconciles textual discrepancies in his writings and on the other throws new light on many of the previous interpretations. In order to accomplish this goal, I draw distinctions between four perspectives, from which the philosopher considers this issue in his writings. This allows me to give the final form of Kant’s world peace, explain the character of the international state of nature vs the original (interpersonal) one, and understand the role of the principles of politics and the status of Kant’s teleological understanding of history.